Perception of Agricultural Input Dealers and Challenges Faced by them in Selling Kitchen Garden Pouch in Anand District of Gujarat, India - , Karshan Chavda, Deval B. Patel (Archives of Current Research International, 2024)
Micronutrient deficiencies are a significant issue in countries like India, impairing physical and cognitive development. Therefore, overcoming this requires effective and efficient strategies that use available resources and have long term benefits are needed. Kitchen gardening, a traditional practice, is gaining popular as a solution. Kitchen garden seed pouches simplify gardening, promoting self-sufficiency and sustainability, even in limited spaces. These pouches contain quality seeds of popular vegetables and herbs. This study was conducted with three objectives, to study profile of agricultural input dealers, their perception regarding kitchen garden pouch and identify challenges faced by them for selling kitchen garden pouch. It was conducted from January 15th to April 16th 2024 in Anand district of Gujarat and 120 agricultural input dealers were surveyed with the help of semi-structured schedule. Non-Probability sampling method and Convenience sampling was used. Statistical tool like percentage and henry garret ranking methods were used. It reveals that the majority of dealers are middle-aged, with significant experience in the field. Educational qualifications vary, but a significant proportion holds qualifications equivalent to Diploma. The majority operate as retailers, predominantly in urban areas, specializing in seeds and agrochemicals. Despite a high level of awareness about kitchen garden pouches among dealers, a considerable percentage were not actively sold this product. Consumer demand and product quality were key factors influence the dealers’ decision. Challenges faced during product ordering include credit facility and product replacement concerns, challenges at the time of selling product were customer debit behaviour and product price sensitivity.